Coordination chemistry of 3- and 4-mercaptobenzoate ligands: Versatile hydrogen-bonding isomers of the thiosalicylate (2-mercaptobenzoate) ligand - Tiekink, Edward R. T. *; Henderson, William (Elsevier, 2017)
This review summarises the coordination chemistry of the isomeric 3- and 4-mercaptobenzoate ligands, derived from HSC6H4COOH, being isomers of the widely-studied 2-mercaptobenzoate (thiosalicylate) ligand. The 3- and 4-mercaptobenzoate ligands show a wide range of coordination modes, including monodentate (through either S or less commonly O), chelation through the carboxylate group alone, as well as a wide range of bridging modes. However, S,O-chelation, which is prevalent for thiosalicylate complexes, is not found in the 3MBA and 4MBA isomers. In the solid-state, complexes of 3MBA and 4MBA ligands containing protonated carboxylic acid groups typically undergo aggregation through formation of classical hydrogen-bonded carboxylic acid dimer motifs, which can be supplemented by additional interactions such as aurophilic (Au Au) interactions in the case of gold(I) complexes. The hybrid hard-soft nature of 3MBA and 4MBA ligands facilitates the use of these ligands in the construction of early-late heterobimetallic complexes. These ligands also find numerous applications (such as the protection of metallic gold and silver nanoparticles), which are especially prevalent for 4MBA where the para carboxylate/carboxylic acid group is remote from the sulfur coordination site.